RTN4IP1 Is Down-Regulated in Thyroid Cancer and Has Tumor-Suppressive Function - Rahbari, Reza (Endocrine Society, 2013)
CONTEXT: Previously we identified RTN4IP1 to be differentially expressed in thyroid cancer by sex and the gene is located on chromosome 6q21, a chromosomal region frequently deleted or with loss of heterozygosity in a variety of human malignancies including thyroid cancer. OBJECTIVE: Because the expression and function of this gene is unknown, we sought to characterize its expression in normal, hyperplastic, and benign and malignant thyroid tissue samples and to evaluate its function in cancer cells. DESIGN: RTN4IP1 expression was analyzed in normal and hyperplastic thyroid tissue and benign and malignant thyroid tissue samples. In 3 thyroid cancer cell lines (TPC1 from a papillary thyroid cancer, FTC133 from a follicular thyroid cancer, XTC1 from a Hürthle cell carcinoma), small interfering RNA knockdown of RTN4IP1 was used to determine its role in regulating the hallmarks of malignant cell phenotype (cellular proliferation, migration, apoptosis, invasion, tumor spheroid formation, anchorage independent growth). RESULTS: We found RTN4IP1 mRNA expression was significantly down-regulated in follicular and papillary thyroid cancer as compared with normal, hyperplastic, and benign thyroid neoplasms (P < .05). Moreover, RTN4IP1 mRNA expression was significantly lower in larger papillary thyroid cancers (P < .05). Small interfering RNA knockdown of RTN4IP1 expression increased cellular proliferation (2- to 4-fold) in all 3 of the cell lines tested and increased cellular invasion (1.5- to 3-fold) and migration (2- to 7.5-fold), colony formation (3- to 6-fold), and tumor spheroid formation (P < .05) in 2 of the 3 cell lines tested (FTC-133 and XTC1). CONCLUSIONS: This is the first study to characterize the expression and function of RTN4IP1 in cancer. Our results demonstrate RTN4IP1 is down-regulated in thyroid cancer and is associated with larger papillary thyroid cancer and that it regulates malignant cell phenotype. These findings, taken together, suggest that RTN4IP1 has a tumor-suppressive function and may regulate thyroid cancer progression.